Effects of ASEAN Free Trade Area (AFTA) on intra-regional trade flows: Evidence from automotive industry - Lê, Minh Phượng (2020)
This thesis analyses the impact of the ASEAN Free Trade Area (AFTA) on the intra-regional trade flows in the case of the automotive industry. By the gravity model and panel data approach at disaggregated level for 26 years from 1993 to 2018 between 870 pair countries, the study considered the common important issues of gravity model which lead to biased estimation results in popular models. The most important method to control the effects of unobservable variables due to multilateral resistance terms, endogeneity of trade policy and non-discriminatory trade policy is applying high-dimensional fixed effects (HDFE). Meanwhile, Poisson pseudo-maximum likelihood (PPML) model combine with HDFE method performs better estimation results in the case a lot of zeros, heteroskedasticity issue. Also, log-linear method in REGHDFE models to avoid the problem of functional misspecification from PPML suggested that REGHDFE with only time effects is appropriate model to examine the trade creation and trade diversion by AFTA dummies. The reduction of tariff calculated by the difference between MFN and CEPT Scheme under AFTA was also found to have a significant effect in increasing trade volume among AFTA members. Moreover, a comparison of the magnitude of tariff elimination by individual has resulted significantly different effects of tariff between original and new AFTA member.